Analisis Human Error Proses Produksi Menggunakan Metode Fuzzy Heart Pada I.M Interior - Silvia Herawati; Yudi Sukmono; Theresia Amelia Pawitra (Peneliti.net, 2023)
I.M interior is one of the local furniture industries with kitchen sets as their flagship product. Industrial development encourages an industry to produce furniture with good quality at affordable prices and with good and fast service, in this case humans have a very important role, but humans often make mistakes in their work which is called human error. Based on the data obtained using the HTA, the kitchen set has 7 stages of the production process with 22 sub-tasks and each task has the possibility of error. Based on the HEART fuzzy analysis, 3 sub-tasks were obtained which had high Human Error Probability values, namely task 2.1 assembling the body and frame into a cabinet body with a HEP value of 0.336, task 3.4 cutting the remaining outer HPL with a value of 0.598 and task 7.1 making hinge holes with a HEP value of 0.394 . Analysis of the 5 why method is used to find out the root cause of the error occurrence problem. Recommendations for fixing errors are providing training, increasing performance monitoring and making SOP. Keywords: human error, HTA, fuzzy, HEART, 5 why methode, kitchen set